Relationship between maintenance of occlusal support achieved by home‐visit dental treatment and prognosis in home‐care patients—a preliminary study. Issue 11 (20th September 2022) - Kikutani, Takeshi; Takahashi, Noriaki; Tohara, Takashi; Furuya, Hiroyasu; Tanaka, Kumi; Hobo, Kimiko; Isoda, Tomoko; Fukui, Tomoko
Abstract : Aim: To determine whether occlusal maintenance and reconstruction by dental intervention is associated with the prognosis of older home‐care patients. Methods: The study participants were 289 older home‐care patients (101 males, mean age 82.2 ± 7.7 years) who received visiting dental treatment from dental clinics in the region between 2012 and 2018. The participants were followed up for 1000 days after receiving the necessary dental treatment in a home‐visit setting. The participants were divided into three groups: those with natural tooth occlusion, those whose molar occlusion was maintained or reconstructed by dentures, and those whose occlusion was not reconstructed. Factors associated with prognosis were determined using the Cox proportional hazard model, with occlusal status, comorbidities, the activity of daily living, and residence status as explanatory variables. Results: In the overall population, occlusal status (hazard ratio [HR] of those with occlusal disintegration versus those with natural tooth occlusion: 2.1, confidence interval [95% CI]: 1.18–3.82) and age (HR: 2.28, 95% CI: 1.44–3.61) were identified as significant factors. In the group of participants aged <85 years, only occlusal status (HR of those with occlusal disintegration versus those with natural tooth occlusion: 3.4, 95% CI: 1.34–8.68) was a significant factor. In the group of participants aged ≥85 years, occlusal status was not significantly associated with prognosis. Conclusions: The maintenance and acquisition of occlusal support achieved by dental treatment contribute to improved prognosis in older patients younger than 85 years requiring home nursing care. Geriatr Gerontol Int 2022; 22: 976–981 .